2017
DOI: 10.1186/s40249-017-0353-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, access and utilization of bed-nets among stable and seasonal migrants in an artemisinin resistance containment area of Myanmar

Abstract: BackgroundMyanmar lies in the Greater Mekong sub-region of South-East Asia faced with the challenge of emerging resistance to artemisinin combination therapies (ACT). Migrant populations are more likely than others to spread ACT resistance. A vital intervention to reduce malaria transmission, resistance spread and eliminate malaria is the use of bed nets. Among seasonal and stable migrants in an artemisinin resistance containment region of Myanmar, we compared a) their household characteristics, b) contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
(24 reference statements)
3
18
0
Order By: Relevance
“…Overall, a pooled estimate was 44% (95% CI 35–52%), indicating less than half of the targeted MMPs used ITNs. A subgroup of five studies conducted in Myanmar [ 35 , 37 , 39 , 51 , 54 ] also showed similar results (47%, 95% CI 28–66%) (Fig. 5 ).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Overall, a pooled estimate was 44% (95% CI 35–52%), indicating less than half of the targeted MMPs used ITNs. A subgroup of five studies conducted in Myanmar [ 35 , 37 , 39 , 51 , 54 ] also showed similar results (47%, 95% CI 28–66%) (Fig. 5 ).…”
Section: Resultssupporting
confidence: 58%
“…The key characteristics of the included studies are provided in Table 1 . Eleven studies (30.5%) were from Myanmar [ 20 , 25 , 26 , 35 37 , 39 , 48 , 51 , 54 , 55 ], four studies (11.1%) from Cambodia [ 22 , 40 , 43 , 52 ], three studies from French Guiana [ 45 , 46 , 48 ] and two studies each from China [ 15 , 50 ], Thailand [ 23 , 27 ], Sri Lanka [ 28 , 32 ] and Uganda [ 24 , 33 ]. The remaining ten single studies were done in Columbia [ 43 ], Congo [ 44 ], Ethiopia [ 41 ], Lao [ 52 ], Malaysia [ 38 ], Namibia [ 34 ], Pakistan [ 31 ], Sierra Leone [ 29 ], Suriname [ 30 ] and South America [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative data also suggested some of the mobile/migrant workers as multi-task holders and their circular and multidirectional movements, reduced their opportunities to contact health staff and malaria volunteers. Short transitory stays among seasonal migrant workers in Bago Region were noted as one of the challenges of the treated-net distribution programme for MMPs [ 16 ]. Similarly, underexposure and low access to malaria interventions was noted among seasonal workers in Pailin Province, Cambodia [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the NMCP purposively selected townships with significant numbers of migrant workers in six endemic regions. A ratio of 1:2 was considered in selecting migrant clusters classified as categories 1 and 2, versus category 3 [ 15 , 16 ]. Then, a random sample of migrant households in specific categories was selected in three rounds of surveys, reaching a total of 9603.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation